Load of abrasive reinforced wheels when changing technological parameters - Abrashkevych, Yuri; Marchenko, Alexander (Transfer of innovative technologies, 2021)
Abrasive reinforced wheels in combination with the use of manual and stationary grinding machines are widely used in construction and installation work and are among the most common types of hand tools. Domestic and foreign manufacturers of abrasive tools offer products for cutting, cleaning and grinding operations with different design and physical and mechanical properties for processing various materials. The optimal choice of technological and technical parameters of machines, combined with the correct selection of the required abrasive working tool, allows to reduce labor intensity and increase productivity and quality of work with the desired effect [1 ... 4]. It should be noted that the work of such machines is often carried out in an awkward position, at the cost of large additional and unreasonable efforts at high speeds of operations. The process of working with manual grinding machines (including those with abrasive reinforced wheels) has a number of features, they include: instability of the supply in size and direction; continuous change within the allowable power of the drive intensity of the work process; limiting the forces arising at the point of contact of the working tool (abrasive reinforced circle) with the working environment, both the power of the drive and the individual physiological data of the operator. The task of improving working conditions, improving the efficiency of the use of machines for construction and installation work and ensuring the safe operation of the operator requires a comprehensive assessment of the production environment of operators, taking into account the principles of ergonomics. With a clear shortage of manpower during construction and installation and repair work, such a factor in increasing labor productivity as maximum use of labor resources through the creation of comfortable working conditions and the involvement of ergonomically sound tools and its mode of operation can no longer be ignored. -ся. The analysis carried out by the authors [5, 6] of interaction in the system "operator - machine - working environment" when working with angle grinders equipped with cutting and cleaning abrasive reinforced working bodies shows a close relationship between the load on the working body and effort which are perceived by the machine operator, due to the significant influence of the operating parameters. Determining the load on the working body, based on technological conditions is an urgent task, as in the process of abrasive reinforced wheels torque on the spindle and rotation of the working body is created by the drive of the machine, and all other functions - longitudinal and transverse feed, maintenance of the car and general management - are carried out by the operator. When working with hand grinders, the operator can hold it in any position and ensure a sufficiently precise feed direction of the wheel.